DermMeister for the PDA - Richard Usatine (Association of American Medical Colleges, 2006)
Abstract DermMeister is a high-resolution photographic atlas of common skin conditions formatted for personal digital assistants (PDAs). It includes information and images regarding 66 dermatological disorders and step-by-step photos detailing two skin surgery procedures, summing up to over 500 high-resolution photographs. Most of the photos in DermMeister were taken by the author, Dr. Richard Usatine. Other photos are used courtesy of the Skin Cancer Foundation. The text was adapted from the online Interactive Dermatology Atlas. Dr. Usatine is also the lead author of Skin Surgery: A Practical Guide; the editor of Photo Rounds, a regular feature in the Journal of Family Practice; and the founder of the Interactive Dermatology Atlas online. The concept, design, and layout of DermMeister were developed by Dr. Andrew Schechtman, the founder of MeisterMed and author of the Meister series.